PENGARUH PERMAINAN KELOMPOK DALAM KONSELING TERHADAP PEMBENTUKAN KARAKTER ANAK MUALAF - Irman Irman (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2019)
Students from among converts experience psychological problems because they are conducting a process of finding identity and character building. Problems experienced by converts are considered necessary to do an intervention by teachers who are in school. One technique that is deemed appropriate to shape the character of converts is through group work in counseling. The purpose of the study is to reveal the influence of group games in counseling on the formation of the character of converts. The research method used pre-experiment with the one-group pretest-posttest design. Data analysis used paired t test. The results of the study found that (1) there was an increase in the character of converts to a better direction, (2) there was a significant effect of group play in counseling on improving the character of converts.